Effect of Work Discipline and Work Environment on Employee Performance with Work Motivation as an Intervening Variable in Department of Tourism, Youth and Sport of Padang District - Kurniawan, Harry; Heryanto, Heryanto (Archives of Business Research, 2019)
This study aims to determine whether there is an influence of work discipline, work environment on employee performance with work motivation as an interverning variable. The sample selection was done by purposive sampling with a total sample of 65 employees of the Padang Pariaman District Tourism, Youth and Sports Agency. The variables in this study consisted of work discipline variables and work environment as independent variables and employee performance as the dependent variable and work motivation as intervening variables. The data analysis technique used in this study is path analysis. Testing the first hypothesis shows the results that work discipline does not have a significant effect on employee work motivation. Second hypothesis indicate that the work environment has a significant influence on employee motivation. Third hypothesis indicate that work discipline does not influence employee performance significantly. Fourth hypothesis indicate that the work environment has a significant influence on employee performance. Fifth hypothesis indicate that work motivation has a significant influence on employee performance. Sixth hypothesis indicate indirectly work discipline through work motivation has a significant influence on employee performance. And the results of the last hypothesis show that indirectly the work environment through work motivation has a significant influence on the performance of employees at the Tourism and Youth Tourism Office of Padang Pariaman Regency.